1971
DOI: 10.1073/pnas.68.4.773
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Neighboring Base Pairs upon Base-Pair Substitution Mutation Rates

Abstract: The 2-aminopurine-induced transition,A T --G C, was studied at particular sites in bacteriophage T4 as a function of the nearby base-pair composition of the DNA. Changing a base pair changed the transition rate at the adjacent base pair up to 23-fold, and at the next base pair by a lesser amount. Destabilization was achieved by replacing an A -T base pair by a G C base pair.The base-pair substitution mutation rate at a particular genetic site is often thought to depend not only upon the base pair at that site,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1973
1973
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Topal et al (1980) concluded, on the basis of in vitro competition experiments with DNA polymerase, that nearest-neighbor interactions between incoming dNTPs and the terminal base of the nascent strand influence the frequency of substitution mutations. Variable frequencies of 2-aminopurine-induced transitions found by Koch (1971) suggest a dependence on sequence context. Mendelman et al (1989) found that the kinetics of nucleotide misincorporation by DNA polymerase a is dependent on nearest-neighbor base stacking.…”
Section: Discussionmentioning
confidence: 98%
“…Topal et al (1980) concluded, on the basis of in vitro competition experiments with DNA polymerase, that nearest-neighbor interactions between incoming dNTPs and the terminal base of the nascent strand influence the frequency of substitution mutations. Variable frequencies of 2-aminopurine-induced transitions found by Koch (1971) suggest a dependence on sequence context. Mendelman et al (1989) found that the kinetics of nucleotide misincorporation by DNA polymerase a is dependent on nearest-neighbor base stacking.…”
Section: Discussionmentioning
confidence: 98%
“…The experimental modification of site-specific mutation rates by changes in neighboring bases has been studied both in vitro (Kunkel and Soni 1988;Bebenek et al 1993) and in vivo in T4, where Koch (1971) was the first to demonstrate changes in site-specific mutation rates when their neighboring bases were altered. At least in the cases of T4 (which lacks conventional DNA mismatch repair) and of DNA synthesis in vitro by various polymerases, the rate of formation and/or disposition of a mismatch during synthesis can reasonably be expected to vary as a function of its close neighbors, but the number of template and primer bases contacted by the polymerase and/or proofreading exonuclease is small, so the effects of more distant bases might be expected to extinguish quickly.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the thyP3 -based conclusion that conflicts predominantly generate promoter mutations should only be considered with these caveats in mind. All reporter systems therefore have fundamental constraints that need to be carefully considered if one is investigating mutational footprints, especially given that sequence context is well known to affect mutagenesis as well (22). So how can one accurately determine the nature of mutations caused by conflicts?…”
Section: The Role Of Conflicts In Mutagenesis and Evolutionmentioning
confidence: 99%